Adiponectin Decreases Gastric Smooth Muscle Cell Excitability in Mice - Idrizaj, Eglantina; Garella, Rachele; Castellini, Giovanni; Francini, Fabio; Ricca, Valdo; Baccari, Maria Caterina; Squecco, Roberta (Frontiers in Physiology, 2019)
Some adipokines known to regulate food intake at central level can also affect gastrointestinal motor responses. These are recognized to be peripheral signals able to influence feeding behaviour as well. In this view, it has been recently observed that adiponectin (ADPN), which seems to have a role in sending satiety signals at the central nervous system level, actually affects the mechanical responses in gastric strips from mice. However, at present, there are no data in the literature about the electrophysiological effects of ADPN on gastric smooth muscle. To this aim, we achieved experiments on smooth muscle cells (SMCs) of gastric fundus to find out a possible action on SMC excitability and on membrane phenomena leading to the mechanical response. Experiments were made inserting a microelectrode in a single cell of a muscle strip of the gastric fundus excised from adult female mice. We found that ADPN was able to hyperpolarize the resting membrane potential, to enhance the delayed rectifier K+ currents and to reduce the voltage-dependent Ca2+ currents. Our overall results suggest an inhibitory action of ADPN on gastric SMC excitation-contraction coupling. In conclusion, the depressant action of ADPN on the gastric SMC excitability, here reported for the first time, together with its well known involvement in metabolism, might lead us to consider a possible contribution of ADPN also as a peripheral signal in the hunger-satiety cycle and thus in feeding behaviour.